2017
DOI: 10.1002/ps.4560
|View full text |Cite
|
Sign up to set email alerts
|

Sea lice infestation levels decrease with deeper ‘snorkel’ barriers in Atlantic salmon sea‐cages

Abstract: Deeper snorkels dramatically and consistently reduced infection levels of salmon lice compared with shallow snorkels, without consequences for fish welfare and production performance. Therefore, reducing salmon sea lice encounters using a depth-based barrier is a powerful management tool for salmon farming. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 59 publications
(127 reference statements)
3
38
1
Order By: Relevance
“…Fish welfare indicators and weights were similar between snorkel and standard cages, including where snorkels were filled with freshwater, confirming conclusions reached in previous snorkel cage investigations that use of this technology does not affect fish welfare (Oppedal et al 2017. Snout damage, likely due to collisions with net roof and snorkel structures, has been observed in one research scale snorkel cage study (Stien et al 2016) but we did not observe this negative effect here.…”
Section: Effects Of Standard Sw and Fw Snorkels Cages On Fish Welfarsupporting
confidence: 90%
See 2 more Smart Citations
“…Fish welfare indicators and weights were similar between snorkel and standard cages, including where snorkels were filled with freshwater, confirming conclusions reached in previous snorkel cage investigations that use of this technology does not affect fish welfare (Oppedal et al 2017. Snout damage, likely due to collisions with net roof and snorkel structures, has been observed in one research scale snorkel cage study (Stien et al 2016) but we did not observe this negative effect here.…”
Section: Effects Of Standard Sw and Fw Snorkels Cages On Fish Welfarsupporting
confidence: 90%
“…While harvest-sized salmon have been found to position themselves almost exclusively below 4 m deep SW snorkels in identical cages in autumn (Stien et al 2016), periodic post-smolt presence inside 4 to 16 m deep SW snorkels, inferred from low oxygen conditions, was detected by Oppedal et al (2017). Therefore, greater fish residency inside SW snorkels may contribute to lice reduction effects typically seen in this cage type (see Oppedal et al 2017). More work is needed to reveal differences in depth distribution of Atlantic salmon among standard, SW and FW snorkel cage types.…”
Section: Effects Of Standard Sw and Fw Snorkel Cages On Salmon Licementioning
confidence: 99%
See 1 more Smart Citation
“…School swimming distance from the halocline was also found to be an important factor of susceptibility in commercial cages, whereby peaks of infestation in control cages were estimated to have occurred when the school was swimming within 5 m of the halocline (Bui et al 2018). This relationship between host exposure to surface waters and susceptibility to infestation is further supported by the results of Oppedal et al (2017), where infestation rates decreased exponentially with increasing barrier depth. Studies that have used depth-based pre- Frequency (%) 0-1 1-2 2-3 3-4 4-5 5-6 6-7 7-8 8-9 9-10 10-11 10-12 Snorkel Control Snorkel base Fig.…”
Section: Effects Of Lice Barriers On Salmon Lice Infestation Levelsupporting
confidence: 55%
“…Little or no adverse effects on fish mortality and welfare were detected. Oppedal et al (2017) tested how varying snorkel depths affected lice infestation levels, and found that as snorkel depth increased (0, 4, 8, 12, and 16 m), lice infestations decreased exponentially. Growth, condition, mortality, swimming speeds, and key welfare indices were similar for all snorkel depths .…”
Section: Introductionmentioning
confidence: 99%